Reducing the incidence and mortality of traumatic brain injury in Latin America - Rivera-Lara, Lucia; Videtta, Walter; Calvillo, Eusebia; Mejia-Mantilla, Jorge; March, Karen; Ortega-Gutierrez, Santiago; Obrego, Guadalupe Castillo; Paranhos, Jorge E.; Suarez, Jose I. (European journal of trauma and emergency surgery (Munich : 2007), 2023)
Traumatic brain injury (TBI) represents a considerable portion of the global injury burden. The incidence of TBI will continue to increase in view of an increase in population density, an aging population, and the increased use of motor vehicles, motorcycles, and bicycles. The most common causes of TBI are falls and road traffic injuries. Deaths related to road traffic injury are three times higher in low-and middle-income countries (LMIC) than in high-income countries (HIC). The Latin American Caribbean region has the highest incidence of TBI worldwide, primarily caused by road traffic injuries. Data from HIC indicates that road traffic injuries can be successfully prevented through concerted efforts at the national level, with coordinated and multisector responses to the problem. Such actions require implementation of proven measures to address the safety of road users and the vehicles themselves, road infrastructure, and post-crash care. In this review, we focus on the epidemiology of TBI in Latin America and the implementation of solutions and preventive measures to decrease mortality and long-term disability.